A Study On The Effect Of Separate Versus Integrated Vocabulary Learning Strategies Instruction On Iranian Male And Female EFL Learners' Vocabulary Learning - Seyfaddini, Peyman (2010)
As research on the effectiveness of integrated and separate methods of learning strategies is inconclusive and researchers have determined that female and male students perform differently in language classes and use different strategies for learning a language, this study examines which method, integrated or separate, is more effective for teaching vocabulary learning strategies to Iranian male and female high school students. One hundred and fifty third grade high school students from six classes in two large boys and girls high schools were involved in the study during the spring semester. There were fifty students in two control groups and one hundred in four experimental groups. Both the control and experimental groups received the vocabulary pre-test. Subsequently, Schmitt‟s (1999) vocabulary learning strategies questionnaire was administered to the experimental groups and the strategies that were appropriate to be learned by the subjects were selected. The strategies were selected considering the way the subjects claimed they used them. For utilizing the integrated method the selected strategies were taught by a teacher to a girls‟ class and a boys‟ class along with their regular English class sessions. For administering the separate method, the researcher taught the selected strategies to a girls‟ class and a boys‟ class in separate classes from the regular English language classes. This took six sessions during the first two weeks of the semester. The same teacher who utilized a traditional teaching approach with the control groups and the integrated approach ran the regular English language class for the separate group. At the end of the semester all the experimental and control groups received a vocabulary post-test and the effectiveness of vocabulary learning strategies instruction was determined. The separate method was found to be more effective for the female students and the integrated one was more effective for the males. In addition, interviews were conducted that further corroborated the results.